Molar Concentrations of Fibrinolytic Components, Especially Free Fibrinolysin, in Vivo - Nanninga, L. B (Thrombosis and Haemostasis, 1975)
The levels of fibrinogen and of Profibrinolysin (plasminogen) in urokinase-treated plasma as a function of time of incubation were measured. The Profibrinolysin concentration was estimated through its complete conversion to fibrinolysin and the inhibition of the enzyme by crystalline soybean trypsin inhibitor. The dissociation constant of the FL-STX complex was determined to be 7 × 10–9 M. The average concentration of Profibrinolysin in normal human citrated plasma was found to be 8 × 10–7 M. From the decrease of fibrinogen with time in the urokinase-treated plasma, the free fibrinolysin was calculated. Free fibrinolysin in normal human blood in vivo was estimated from the half-life of fibrinogen and other data obtained in this study to be present at a concentration of 1.7 × 10–10 M. The plasmakinase activity in vivo, expressed as urokinase molarity, is also about 2 × 10–10 M.